Outcome of children and adolescents with Down syndrome treated on Dana‐Farber Cancer Institute Acute Lymphoblastic Leukemia Consortium protocols 00–001 and 05‐001. Issue 10 (7th June 2018) - Athale, Uma H.; Puligandla, Maneka; Stevenson, Kristen E.; Asselin, Barbara; Clavell, Luis A.; Cole, Peter D.; Kelly, Kara M.; Laverdiere, Caroline; Leclerc, Jean‐Marie; Michon, Bruno; Schorin, Marshall A.; Sulis, Maria Luisa; et al.
Abstract: Background: Children and adolescents with Down syndrome (DS) and acute lymphoblastic leukemia (ALL) are reported to have increased relapse rates and therapy‐related mortality (TRM). Treatment regimens for DS‐ALL patients often include therapy modifications. Dana‐Farber Cancer Institute (DFCI) ALL Consortium protocols have used same risk‐stratified treatment for patients with and without DS. Procedures: We compared clinical and outcome data of DS (n = 38) and non‐DS (n = 1, 248) patients enrolled on two consecutive DFCI ALL trials 00–001 (2000–2004) and 05‐001 (2005–2011) with similar risk adapted therapy regardless of DS status. Results: There was no difference in demographic or presenting clinical features between two groups except absence of T‐cell phenotype and lower frequency of hyperdiploidy in DS‐ALL group. All DS‐ALL patients achieved complete remission; four relapsed and one subsequently died. There was no TRM in DS‐ALL patients. DS‐ALL patients had significantly higher rates of mucositis (52% vs. 12%, p  < 0.001), non‐CNS thrombosis (18% vs. 8%; p  = 0.036), and seizure (16% vs. 5%, p  = 0.010). Compared to non‐DS‐ALL patients, DS‐ALL patients had a higher incidence of infections during all therapy phases. The 5‐year event‐free and overall survival rates of DS‐ALL patients were similar to non‐DS‐ALL patients (91% [95% confidence interval (CI), 81–100] vs. 84% [95% CI, 82–86]; 97% [95% CI, 92–100] vs. 91% [95% CI, 90–93]). Conclusion: The low rates of relapse and TRM indicate that uniform risk‐stratified therapy for DS‐ALL and non‐DS‐ALL patients on DFCI ALL Consortium protocols was safe and effective, although the increased rate of toxicity in the DS‐ALL patients highlights the importance of supportive care during therapy.